A triply cloned strain of Xylella fastidiosa multiplies and induces symptoms of citrus variegated chlorosis in sweet orange - Li, W. B.; Zreik, L.; Fernandes, N. G.; Miranda, V. S.; Teixeira, D. C.; Ayres, A. J.; Garnier, M.; Bove, J. M. (Springer, 1999)
Xylella fastidiosa isolate 8.1,b obtained from a sweet orange tree affected by citrus variegated chlorosis in the state of Sb Paulo, Brazil, and shown in 1993 to be the causal agent of the disease, was cloned by repeated culture in liquid and on solid PW medium, yielding triply cloned strain 9a5c. The eighth and the 16th passages of strain 9a5c were mechanically inoculated into sweet orange plants. Presence of X. fastidiosa in sweet orange leaves of shoots having grown after inoculation (first-flush shoots) was detected by DAS-ELISA and PCR. Thirty-eight days after inoculation, 70% of the 20 inoculated plants rested positive, and all plants gave strong positive reactions 90 days after inoculation. Symptoms first appeared after 3 months and were conspicuous after 5 months. X. fastidiosa was reisolated from sweet orange leaves, 44 days after inoculation. These results indicate that X. fastidiosa strain 9a5c, derived from pathogenic isolate 8.1.b by triply cloning, is also pathogenic, Strain 9a5c is now used for the X. fastidiosa genome sequencing project undertaken on a large scale in Brazil.